THE INFLUENCE OF FLOOD AND WITHERING PROCESSES FOR THE MINERALOGICAL STRUCTURE OF THE TERSKO SULAKAY LOWLAND’S LIGHT CHESTNUT SOILS - M. E. Kotenko (Юг России: экология, развитие, 2014)
The qualitative mineralogical structure of flood and withering light chestnut soils of West Pricaspiy`s arid zone was deter-mined by the method of radio diffraction. The presence of the quartz, field spar, mica, peach, carbonates and gypsum was discovered. It is established that the periods of flood and withering didn’t influenced for the qualitative mineralogical structure.